2014
DOI: 10.1152/ajpcell.00030.2014
|View full text |Cite
|
Sign up to set email alerts
|

N-glycosylation and topology of the human SLC26 family of anion transport membrane proteins

Abstract: Li J, Xia F, Reithmeier RA. N-glycosylation and topology of the human SLC26 family of anion transport membrane proteins. Am J Physiol Cell Physiol 306: C943-C960, 2014. First published March 19, 2014 doi:10.1152/ajpcell.00030.2014.-The human solute carrier (SLC26) family of anion transporters consists of 10 members (SLCA1-11, SLCA10 being a pseudogene) that encode membrane proteins containing ϳ12 transmembrane (TM) segments with putative N-glycosylation sites (-NXS/T-) in extracellular loops and a COOHtermin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 71 publications
8
24
0
Order By: Relevance
“…However, most of NKCC2 from COS7 cells (densitometrically estimated 80–90%) appeared as core/high mannose (~120 kDa) and hybrid-type N-glycans (~135 kDa), whereas the complex N-glycosylated version of the transporter (~160 kDa) was barely detected. These results are consistent with the relatively low expression levels of the transporter in these cells and with the concept that complex N-glycosylation depends on the level of cargo reaching the complex N-glycosylation machinery of the Golgi, as has been suggested for many proteins (Stanley, 2011), including NKCC1 in COS7 cells (Singh et al, 2015) and other ion transporters (Li et al, 2014). The low levels, or even absence, of complex N-glycosylated NKCC2 is consistent with the cellular distribution of the co-transporter in COS7 cells, where most of the endogenous NKCC2 appeared localized in intracellular compartments but not in the plasma membrane.…”
Section: Discussionsupporting
confidence: 90%
“…However, most of NKCC2 from COS7 cells (densitometrically estimated 80–90%) appeared as core/high mannose (~120 kDa) and hybrid-type N-glycans (~135 kDa), whereas the complex N-glycosylated version of the transporter (~160 kDa) was barely detected. These results are consistent with the relatively low expression levels of the transporter in these cells and with the concept that complex N-glycosylation depends on the level of cargo reaching the complex N-glycosylation machinery of the Golgi, as has been suggested for many proteins (Stanley, 2011), including NKCC1 in COS7 cells (Singh et al, 2015) and other ion transporters (Li et al, 2014). The low levels, or even absence, of complex N-glycosylated NKCC2 is consistent with the cellular distribution of the co-transporter in COS7 cells, where most of the endogenous NKCC2 appeared localized in intracellular compartments but not in the plasma membrane.…”
Section: Discussionsupporting
confidence: 90%
“…Recently, the structure of SLC26 proteins has been reviewed . SLC26 proteins have three distinct regions: a variable cytoplasmic N‐terminal region (51–106 amino acids), an integral membrane domain of 12 transmembrane segments, and a cytoplasmic C‐terminal STAS (sulfate transporter and anti‐Sigma factor antagonist) domain related to those found in some bacterial proteins. SLC26 proteins are dimeric , as also seen for SLC4 proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Coe, unpublished). However, since we suspect that ENTs form dimers and we know that glycosylation of other transporters has been correlated with the formation of oligomers [20,21], we investigated the role of glycosylation of ENT1 in the formation of ENT dimers. As predicted, we observed that wt ENT1 co-immunoprecipitated with itself (HA-hENT1 with 3xFLAG-ENT1) but did not co-immunoprecipitate with 3xFLAG-N48Q-ENT1, or 3xFLAG-hLa (Figure 4) suggesting that N48Q mutant ENT1 is unable to form a complex with wt ENT1.…”
Section: Resultsmentioning
confidence: 99%
“…HEK293 (human embryonic kidney cell line), commonly used in membrane protein glycosylation studies [2022], were grown in Dulbecco's Modified Eagle Media (DMEM) supplemented with 10% (v/v) FBS in 10 cm 2 plates [ S -(4-nitrobenzyl)-6-thioinosine (NBTI) binding and Western blotting] or six-well plates (transport assays) at 37°C with 5% (v/v) CO 2 . Cells were transfected using the standard Polyjet protocol (SignaGen Laboratories) and incubated post transfection for ∼36 h. Equivalent transfection efficiency in wild type (wt) and mutant-transfected cells was confirmed by microscopy.…”
Section: Methodsmentioning
confidence: 99%